High-adhesiveness powder coating as well as preparation method and application thereof
By using the combination of light -emitting additives, acetate cellulose, and polar discharge agent containing lipidicate in the powder coatings, the problem of the existing powder coating paint film surface content of the existing powder coating film is significantly improved. The adhesion of the paint film and glass glue meets the installation requirements of the glass panel on the house shell.
Patent Information
- Application Number
- CN202410944022.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-01-28
AI Technical Summary
The existing powder coating for household appliances has low polar groups on the surface, resulting in poor adsorption of glass glue on its surface, which can easily cause the glass panel to fall off and cannot meet the installation requirements of glass panels on the housing of household appliances.
Using high -adhesive powder coatings containing a glory with lipidate, acetic acid cellulose and polar discharge agent, the polar group of these components and the mutual supplement of the polar groups of these components and the epoxy resin and polyester resin And adsorb, improve the adhesion and surface tension on the surface of the paint film.
It significantly enhances the adhesion of the glass glue on the paint film and the glass panel, so that the glass panel is firmly fixed on the shell of the household appliances, and the installation requirements of the glass panel on the house shell of the household appliances are met. Essence
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder coatings, and in particular relates to a high-adhesion powder coating and a preparation method and application thereof. Background Art
[0002] The dispersion medium of powder coating is air, not solvent or water, which makes it have the characteristics of no solvent pollution, 100% film formation and low energy consumption. It is widely used in many fields, especially in the field of household appliances. At present, household appliances such as refrigerators, dishwashers, and range hoods usually install glass panels in their shells in pursuit of visualization. The assembly process of this glass panel is to first spray a layer of powder coating on the surface of the metal frame of the shell, then apply glass glue (such as silicone glass glue) on the edge of the glass panel, and finally, embed the glass panel with glass glue into the metal frame of the shell. Therefore, in the shell of household appliances, the glass panel is directly bonded to the powder coating on the surface of the metal frame through glass glue. The degree of adhesion between glass glue and powder coating directly affects the firmness of the installation of the glass panel in the shell of household appliances.
[0003] In the prior art, there are some powder coatings for household appliances, which focus on improving their decorative performance, weather resistance and water boiling resistance. For example, Chinese patent CN112852252A discloses a powder coating for household appliances, which includes 25-35 parts of epoxy resin, 25-35 parts of polyester resin, 3-5 parts of curing agent, 5-10 parts of other additives, 3-8 parts of pigment, 15-40 parts of filler and 0.1-0.5 parts of antioxidant. This powder coating has the characteristics of high leveling performance, excellent temperature resistance, excellent bonding performance, excellent weather resistance, excellent water boiling resistance and safety and non-toxicity. However, the paint film of this powder coating has a small content of polar groups on the surface and low surface tension, so that the glass glue is not firmly adsorbed on its surface, which easily causes the glass panel to fall off, and cannot meet the installation requirements of the glass panel on the shell of the household appliance, thereby affecting the normal production efficiency, performance quality and appearance of the household appliance. Summary of the invention
[0004] The purpose of the present invention is to provide a high-adhesion powder coating and a preparation method and application thereof, aiming to solve the problem in the prior art that the paint film of powder coatings for household appliances has a low content of polar groups on the surface and a low surface tension, which makes the glass glue not firmly adsorbed on its surface and easily causes the glass panel to fall off, thereby failing to meet the installation requirements of the glass panel on the outer shell of the household appliance, thereby affecting the normal production efficiency, performance quality and appearance of the household appliance.
[0005] In order to solve the above technical problems, the present invention is mainly implemented through the following technical solutions:
[0006] In one aspect, a high-adhesion powder coating of the present invention comprises the following components in percentage by weight: 25-35% epoxy resin, 30-40% polyester resin, 1-2% matting agent, 0.3-1.0% cellulose acetate butyrate, 0.5-1% polar leveling agent, 0.3-0.5% benzoic acid ketone, 0.4-0.7% wetting promoter, 5-25% filler, 5-25% titanium dioxide, and 0-1% pigment; the matting agent is a matting agent containing stearate, and the weight percentage of the stearate in the matting agent is 2-10%.
[0007] The matting agent containing stearate of the present invention contains abundant polar groups, namely carboxyl groups, cellulose acetate butyrate contains a large number of polar groups, namely hydroxyl groups, and the polar leveling agent also contains a large number of polar groups, namely hydroxyl groups. These polar groups complement the hydroxyl groups in the epoxy resin and the ester groups in the polyester resin, and effectively make up for the defect of low content of polar groups on the surface of the paint film of the traditional powder coating. Moreover, the carboxyl groups in the matting agent containing stearate, the hydroxyl groups in the cellulose acetate butyrate and the hydroxyl groups in the polar leveling agent closely cooperate with the hydroxyl groups in the epoxy resin and the ester groups in the polyester resin, and adsorb to each other, and migrate to the surface of the paint film when the powder coating is cured. On the surface, it plays a bridging role and improves the adhesion of the paint film surface; in addition, the matting agent containing stearate, cellulose acetate butyrate and polar leveling agent also promotes and coordinates with diphenyl ethyl ketone and wetting promoter to increase the surface tension of the paint film. When used on the shell of household appliances, it increases the contact area between the paint film and the glass glue on the glass panel, greatly enhances the adhesion between the paint film and the glass glue on the glass panel, and firmly fixes the glass panel on the shell of household appliances, meets the installation requirements of the glass panel on the shell of household appliances, realizes the normal production of household appliances, and ensures the performance quality and appearance of household appliances.
[0008] As a preferred embodiment, the average particle size of the high-adhesion powder coating is 35-45 μm. The high-adhesion powder coating of the present invention exists in the state of fine powder. During the spraying process, epoxy resin and polyester resin are used as film-forming substances. During the drying process, the film-forming substances are first melted, and then solidified after chemical cross-linking to form a dense and uniform thermal curing paint film. The polar leveling agent of the present invention is a leveling agent adsorbed by silica with polar group hydroxyl, in particular, a polyacrylate leveling agent adsorbed by silica with polar group hydroxyl; the polar leveling agent can significantly improve the leveling condition of the paint film surface and avoid the formation of shrinkage holes.
[0009] As a preferred embodiment, the wetting promoter is a methyl methacrylate-butyl acrylate copolymer. The wetting promoter of the present invention contains multiple active groups, such as methyl, olefin, carboxyl, and ester groups, and is closely matched with a matting agent containing stearate, cellulose acetate butyrate, a polar leveling agent, and benzoyl ketone, further improving the comprehensive performance of the powder coating, especially the anti-pollution performance.
[0010] As a preferred embodiment, the epoxy resin is a bisphenol A type epoxy resin with an epoxy value of 0.110-0.130eq / 100g. The hydroxyl group in the epoxy resin of the present invention has a high polarity, and the epoxy resin has a high softening point and good impact resistance, and good performance in use.
[0011] As a preferred embodiment, the polyester resin is a carboxyl-terminated saturated polyester resin with an acid value of 45-70 mgKOH / g. The polyester resin of the present invention contains abundant carboxyl groups, has good leveling properties and excellent mechanical properties.
[0012] As a preferred embodiment, the filler is any one or more of barium sulfate, calcium carbonate, and silicon dioxide. The filler of the present invention includes but is not limited to barium sulfate, calcium carbonate, or silicon dioxide, preferably barium sulfate, which can improve the mechanical properties of the paint film and make the paint film surface smooth.
[0013] As a preferred embodiment, the titanium dioxide is rutile titanium dioxide. The rutile titanium dioxide of the present invention can provide excellent hiding power and surface effect for the powder coating, and improve the comprehensive performance of the powder coating.
[0014] As a preferred embodiment, the pigment is a carbon black pigment. The carbon black of the present invention has a wide source, is cheap and easy to obtain, and has good weather resistance. The benzoic acid ketone of the present invention is a non-wax-based degassing agent, does not float, has a large surface tension of the coating film and a strong polarity, and can also eliminate pinholes caused by small molecules generated during the curing reaction breaking through the surface of the coating film, fully ensuring a good appearance of the coating film surface.
[0015] In another aspect, a method for preparing a high-adhesion powder coating of the present invention comprises the following steps: 1) weighing epoxy resin, polyester resin, matting agent, cellulose acetate butyrate, polar leveling agent, benzoyl ketone, wetting promoter, filler, titanium dioxide and pigment, mixing and stirring to obtain a mixture; 2) placing the mixture obtained in step 1) in a twin-screw extruder for melting, mixing and extrusion, wherein the temperature of the first zone of the twin-screw extruder is 100-110° C. and the temperature of the second zone is 110-120° C.; 3) cooling, crushing, grinding and sieving the extruded sheet in step 2) to obtain a high-adhesion powder coating.
[0016] In the preparation method of the high-adhesion powder coating of the present invention, first, the components are mixed uniformly at room temperature, and the mixing can be done manually or by a mixer. The stirring time is controlled according to the actual situation, and the stirring is usually 10-15 minutes to make the components uniformly mixed; then, the components are placed in a twin-screw extruder for melt mixing and extrusion, and the filler, pigment, titanium dioxide, matting agent, cellulose acetate butyrate, polar leveling agent, benzoyl ketone and wetting promoter are fully and evenly dispersed in the epoxy resin and the polyester resin, and are coated and wetted by the epoxy resin and the polyester resin, thereby ensuring the performance of the powder coating; finally, after cooling, crushing, grinding and screening, a powder coating with uniform particle size is obtained. Grinding is usually completed in a grinder, and an ACM series grinder can be selected; under normal circumstances, the main grinding speed of the grinder is 45-50Hz, and the secondary grinding speed is 25-30Hz. Screening removes particles with larger particle sizes, and grinding is performed again to fully control the particle size and uniformity of the powder coating, which is convenient for construction and spraying. The preparation method of the high-adhesion powder coating of the present invention is simple to operate, has low requirements on equipment, has mild process conditions, and is easy to realize industrial production.
[0017] In still another aspect, the invention provides an application of a high-adhesion powder coating, wherein the high-adhesion powder coating is used on a housing of a household appliance.
[0018] The high-adhesion powder coating of the present invention is particularly suitable for spraying onto the housing of household appliances. When a glass panel is installed on the housing of a household appliance using the high-adhesion powder coating, the glass glue on the glass panel and the paint film of the high-adhesion powder coating on the surface of the housing have a large contact area, and the glass glue adsorbs each other through abundant polar groups, resulting in high surface tension and strong bonding force, so that the glass panel is firmly fixed on the housing. The high-adhesion powder coating is particularly suitable for bonding with silicone glass glue, meets the installation requirements of the glass panel on the housing of household appliances, realizes the normal production of household appliances, and ensures the performance quality and appearance of household appliances.
[0019] Compared with the prior art, the present invention has the following beneficial effects: the carboxyl groups in the matting aid containing stearate, the hydroxyl groups in cellulose acetate butyrate and the hydroxyl groups in the polar leveling agent are all polar groups, and these polar groups complement the hydroxyl groups in the epoxy resin and the ester groups in the polyester resin, effectively making up for the defect of low content of polar groups on the surface of the paint film of the traditional powder coating; moreover, the carboxyl groups in the matting aid containing stearate, the hydroxyl groups in cellulose acetate butyrate and the hydroxyl groups in the polar leveling agent closely cooperate with the hydroxyl groups in the epoxy resin and the ester groups in the polyester resin, adsorb to each other, and migrate to the surface of the paint film when the powder coating is cured. On the surface, it plays a bridging role, improving the adhesion of the paint film surface; in addition, the matting aid containing stearate, cellulose acetate butyrate and polar leveling agent also promote each other with diphenyl ethyl ketone and wetting promoter, and the coordinated effect increases the surface tension of the paint film. When used on the shell of household appliances, it increases the contact area between the paint film and the glass glue on the glass panel, greatly enhances the adhesion between the paint film and the glass glue on the glass panel, and makes the glass panel firmly fixed on the shell of the household appliance, meets the installation requirements of the glass panel on the shell of the household appliance, realizes the normal production of the household appliance, and ensures the performance quality and appearance of the household appliance. The preparation method of the high-adhesion powder coating of the present invention is simple to operate, has low equipment requirements, mild process conditions, and is easy to realize industrial production. DETAILED DESCRIPTION
[0020] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The high-adhesion powder coating of the present invention comprises the following components in percentage by weight: 25-35% of epoxy resin, 30-40% of polyester resin, 1-2% of matting agent, 0.3-1.0% of cellulose acetate butyrate, 0.5-1% of polar leveling agent, 0.3-0.5% of benzoic acid ketone, 0.4-0.7% of wetting promoter, 5-25% of filler, 5-25% of titanium dioxide and 0-1% of pigment; the matting agent is a matting agent containing stearate, and the weight percentage of the stearate in the matting agent is 2-10%.
[0022] Preferably, the high-adhesion powder coating has an average particle size of 35-45 μm.
[0023] Preferably, the wetting promoter is methyl methacrylate-butyl acrylate copolymer.
[0024] Preferably, the epoxy resin is a bisphenol A type epoxy resin having an epoxy value of 0.110-0.130 eq / 100 g.
[0025] Preferably, the polyester resin is a carboxyl-terminated saturated polyester resin having an acid value of 45-70 mgKOH / g.
[0026] Preferably, the filler is any one or more of barium sulfate, calcium carbonate and silicon dioxide.
[0027] Preferably, the titanium dioxide is rutile titanium dioxide.
[0028] Preferably, the pigment is a carbon black pigment.
[0029] A method for preparing a high-adhesion powder coating of the present invention comprises the following steps:
[0030] 1) Weigh epoxy resin, polyester resin, matting agent, cellulose acetate butyrate, polar leveling agent, benzoyl ketone, wetting promoter, filler, titanium dioxide and pigment, mix and stir evenly to obtain a mixture;
[0031] 2) placing the mixture obtained in step 1) in a twin-screw extruder for melting, mixing and extrusion, wherein the temperature of the first zone of the twin-screw extruder is 100-110° C. and the temperature of the second zone is 110-120° C.;
[0032] 3) Cooling, crushing, grinding and sieving the sheet extruded in step 2) to obtain a high-adhesion powder coating.
[0033] The invention discloses an application of a high-adhesion powder coating, wherein the high-adhesion powder coating is used on the housing of a household appliance.
[0034] Embodiment 1
[0035] A method for preparing a high-adhesion powder coating of the present invention comprises the following steps:
[0036] 1) Weigh the following components by weight: 25Kg epoxy resin, 40Kg polyester resin, 1.5Kg matting agent, 0.6Kg cellulose acetate butyrate, 0.7Kg polar leveling agent, 0.5Kg benzoyl ketone, 0.7Kg wetting promoter, 5Kg filler, 25Kg titanium dioxide, 1Kg pigment, a total of 100Kg;
[0037] The epoxy resin is a bisphenol A epoxy resin with an epoxy value of 0.130 eq / 100 g, the polyester resin is a carboxyl-terminated saturated polyester resin with an acid value of 45 mgKOH / g, the matting agent is an acrylic matting agent containing 2% by weight of aluminum stearate, the wetting promoter is a methyl methacrylate-butyl acrylate copolymer, the filler is barium sulfate, and the pigment is carbon black;
[0038] 2) Place the above components in a mixer and mix for 10 minutes to ensure that they are fully mixed;
[0039] 3) putting the mixture obtained in step 1) into a twin-screw extruder for melting, mixing and extrusion, wherein the temperature of the first zone of the twin-screw extruder is 100° C. and the temperature of the second zone is 110° C.;
[0040] 4) The extruded sheet in step 3) is cooled, crushed, and ground in an ACM grinder. The main grinding speed of the ACM grinder is 45 Hz, and the secondary grinding speed is 30 Hz. A rotary sieve is used for screening to screen out particles with a particle size of 35-45 μm, i.e., high-adhesion powder coating.
[0041] Embodiment 2
[0042] A method for preparing a high-adhesion powder coating of the present invention comprises the following steps:
[0043] 1) Weigh the following components by weight: 30 kg epoxy resin, 35 kg polyester resin, 1.0 kg matting agent, 0.3 kg cellulose acetate butyrate, 0.5 kg polar leveling agent, 0.3 kg benzoyl ketone, 0.4 kg wetting promoter, 17.5 kg filler, 15 kg titanium dioxide, a total of 100 kg;
[0044] The epoxy resin is a bisphenol A epoxy resin having an epoxy value of 0.120 eq / 100 g, the polyester resin is a carboxyl-terminated saturated polyester resin having an acid value of 55 mg KOH / g, the matting agent is an acrylic matting agent containing 10% by weight of calcium stearate, the wetting promoter is a methyl methacrylate-butyl acrylate copolymer, the filler is calcium carbonate, and the titanium dioxide is rutile titanium dioxide;
[0045] 2) Place the above components in a mixer and mix for 12 minutes to ensure that they are fully mixed;
[0046] 3) putting the mixture obtained in step 1) into a twin-screw extruder for melting, mixing and extrusion, wherein the temperature of the first zone of the twin-screw extruder is 110° C. and the temperature of the second zone is 120° C.;
[0047] 4) The extruded sheet in step 3) is cooled, crushed, and ground in an ACM grinder. The main grinding speed of the ACM grinder is 50 Hz, and the auxiliary grinding speed is 25 Hz. A rotary sieve is used for screening to screen out particles with a particle size of 35-45 μm, i.e., high-adhesion powder coating.
[0048] Embodiment 3
[0049] A method for preparing a high-adhesion powder coating of the present invention comprises the following steps:
[0050] 1) Weigh the following components by weight: 35Kg of epoxy resin, 30Kg of polyester resin, 2.0Kg of matting agent, 1.0Kg of cellulose acetate butyrate, 1.0Kg of polar leveling agent, 0.4Kg of benzoyl ketone, 0.4Kg of wetting promoter, 25Kg of filler, 5Kg of titanium dioxide, 0.2Kg of pigment, a total of 100Kg;
[0051] The epoxy resin is a bisphenol A epoxy resin with an epoxy value of 0.110 eq / 100 g, the polyester resin is a carboxyl-terminated saturated polyester resin with an acid value of 70 mg KOH / g, the grade of the matting agent is SA2065K, the grade of the polar leveling agent is BYK364P, the wetting promoter is a methyl methacrylate-butyl acrylate copolymer, the filler is silicon dioxide, and the pigment is carbon black;
[0052] 2) Place the above components in a mixer and mix for 15 minutes to ensure that they are fully mixed;
[0053] 3) putting the mixture obtained in step 1) into a twin-screw extruder for melting, mixing and extrusion, wherein the temperature of the first zone of the twin-screw extruder is 105° C. and the temperature of the second zone is 115° C.;
[0054] 4) The extruded sheet in step 3) is cooled, crushed, and ground in an ACM grinder. The main grinding speed of the ACM grinder is 50 Hz, and the auxiliary grinding speed is 25 Hz. A rotary sieve is used for screening to screen out particles with a particle size of 35-45 μm, i.e., high-adhesion powder coating.
[0055] Comparative Example 1
[0056] On the basis of Example 1, a common leveling agent, namely a pure acrylic leveling agent, is used to replace the polar leveling agent, and other conditions are the same.
[0057] Weigh the following components in parts by weight: 25Kg of bisphenol A type epoxy resin with an epoxy value of 0.130eq / 100g, 40Kg of terminal carboxyl saturated polyester resin with an acid value of 45mgKOH / g, 1.5Kg of acrylic matting agent with a weight percentage of 2% of aluminum stearate, 0.6Kg of cellulose acetate butyrate, 0.7Kg of pure acrylic leveling agent, 0.5Kg of diphenyl ethyl ketone, 0.7Kg of wetting promoter methyl methacrylate-butyl acrylate copolymer, 5Kg of barium sulfate filler, 25Kg of titanium dioxide, and 1Kg of pigment carbon black, a total of 100Kg.
[0058] The above components were placed in a mixer and mixed for 10 minutes to make them fully mixed; and then placed in a twin-screw extruder for melting, mixing and extrusion. The temperature of the first zone of the twin-screw extruder was 100°C and the temperature of the second zone was 110°C; cooled, crushed, and placed in an ACM grinder for grinding. The main grinding speed of the ACM grinder was 45Hz, and the auxiliary grinding speed was 30Hz. A rotary sieve was used for screening to screen out particles with a particle size of 35-45μm, i.e., control sample 1.
[0059] Comparative Example 2
[0060] On the basis of Example 1, a common matting agent, namely, acrylic matting agent, is used to replace the acrylic matting agent with a weight percentage of 2% of aluminum stearate, and other conditions are the same.
[0061] Weigh the following components in parts by weight: 25Kg of bisphenol A epoxy resin with an epoxy value of 0.130eq / 100g, 40Kg of terminal carboxyl saturated polyester resin with an acid value of 45mgKOH / g, 1.5Kg of acrylic matting agent, 0.6Kg of cellulose acetate butyrate, 0.7Kg of polar leveling agent, 0.5Kg of diphenyl ethyl ketone, 0.7Kg of wetting promoter methyl methacrylate-butyl acrylate copolymer, 5Kg of barium sulfate filler, 25Kg of titanium dioxide, and 1Kg of pigment carbon black, a total of 100Kg.
[0062] The above components were placed in a mixer and mixed for 10 minutes to make them fully mixed; and then placed in a twin-screw extruder for melting, mixing and extrusion. The temperature of the first zone of the twin-screw extruder was 100°C and the temperature of the second zone was 110°C; cooled, crushed, and placed in an ACM grinder for grinding. The main grinding speed of the ACM grinder was 45Hz, and the auxiliary grinding speed was 30Hz. A rotary sieve was used for screening to screen out particles with a particle size of 35-45μm, i.e., control sample 2.
[0063] Comparative Example 3
[0064] On the basis of Example 1, cellulose acetate butyrate is not used, and other conditions are the same.
[0065] Weigh the following components in parts by weight: 25Kg of bisphenol A epoxy resin with an epoxy value of 0.130eq / 100g, 40Kg of terminal carboxyl saturated polyester resin with an acid value of 45mgKOH / g, 1.5Kg of acrylic matting agent with a weight percentage of 2% of aluminum stearate, 0.7Kg of polar leveling agent, 0.5Kg of diphenyl ethyl ketone, 0.7Kg of wetting promoter methyl methacrylate-butyl acrylate copolymer, 5.6Kg of filler barium sulfate, 25Kg of titanium dioxide, and 1Kg of pigment carbon black, a total of 100Kg.
[0066] The above components were placed in a mixer and mixed for 10 minutes to make them fully mixed; and then placed in a twin-screw extruder for melting, mixing and extrusion. The temperature of the first zone of the twin-screw extruder was 100°C and the temperature of the second zone was 110°C; cooled, crushed, and placed in an ACM grinder for grinding. The main grinding speed of the ACM grinder was 45Hz, and the auxiliary grinding speed was 30Hz. A rotary sieve was used for screening to screen out particles with a particle size of 35-45μm, i.e., control sample three.
[0067] Experiment 1
[0068] The three high-adhesion powder coatings obtained in Examples 1 to 3 of the present invention, the control sample 1 obtained in Comparative Example 1, the control sample 2 obtained in Comparative Example 2, the control sample 3 obtained in Comparative Example 3, and the powder coating for household appliances disclosed in Chinese Patent CN112852252A introduced in the background art (control sample 4) were respectively tested for particle size using a LS100Q laser particle size analyzer produced by Beckman Coulter Co., Ltd. The experimental results were expressed as median diameter (D 50 ) are shown in Table 1.
[0069] Table 1 Particle size test results of different powder coatings
[0070] Sample name Embodiment 1 Embodiment 2 Embodiment 3 Control Sample 1 Control Sample 2 Control sample 3 Control Sample 4 Average particle size (μm) 45 42 35 41 39 42 45
[0071] It can be seen from Table 1 that the average particle size of the high-adhesion powder coating obtained by the preparation method of the high-adhesion powder coating of the present invention is 35-45 μm, which is basically consistent with the average particle size of control sample 1, control sample 2, control sample 3 and control sample 4.
[0072] Experiment 2
[0073] Three high-adhesion powder coatings obtained from Examples 1 to 3 of the present invention, as well as Control Sample 1 obtained from Comparative Example 1, Control Sample 2 obtained from Comparative Example 2, Control Sample 3 obtained from Comparative Example 3, and the powder coating for household appliances disclosed in Chinese Patent CN112852252A introduced in the background technology (referred to as Control Sample 4) were sprayed on galvanized sheets using electrostatic spraying technology and the same spraying process parameters, and cured into films in an oven under the same conditions; then, the appearance of the obtained paint film was observed; finally, its mechanical properties were tested. The test items included cross-hatch, pencil hardness, and 60° gloss, and the experimental results are listed in Table 2.
[0074] Among them, in the test items, the cross-cut test is carried out according to the method specified in HGT 2006-2022 Thermosetting and Thermoplastic Powder Coatings, the pencil hardness is tested according to the method specified in GBT 6739-2006 Paints and Varnishes - Determination of Paint Film Hardness by Pencil Method, and the 60° gloss is tested according to the method specified in GBT 9754-2007 Paints and Varnishes - 20°, 60° and 85° specular gloss of paint films without metallic pigments. Use a gloss meter to read 6 numbers at different parts or directions on the coating surface, record them separately, and then take the average value.
[0075] Table 2 Mechanical properties test results of different powder coatings
[0076] Sample name Paint film appearance Crosshatch Pencil hardness 60° gloss Performance requirements The paint film is smooth and even No more than level 1 Not less than H / Embodiment 1 The paint film is smooth and even Level 0 H 32° Embodiment 2 The paint film is smooth and even Level 0 H 35° Embodiment 3 The paint film is smooth and even Level 0 H 30° Control Sample 1 The paint film is smooth and even Level 0 H 33° Control Sample 2 The paint film is smooth and even Level 0 H 34° Control sample 3 The paint film is smooth and even Level 0 H 35° Control Sample 4 The paint film is smooth and even Level 0 H 90°
[0077] As can be seen from Table 2, the surface of the paint film after the high adhesion powder coating obtained by the preparation method of the high adhesion powder coating of the present invention is flat and smooth, which is the same as the control sample 1, the control sample 2, the control sample 3 and the control sample 4. Therefore, the paint film after the high adhesion powder coating of the present invention is sprayed has the same appearance quality as the existing powder coating (control sample 1, the control sample 2, the control sample 3 and the control sample 4). The cross-cutting grade of the paint film after the high adhesion powder coating obtained by the preparation method of the high adhesion powder coating of the present invention is sprayed is 0 grade, which is the same as the control sample 1, the control sample 2, the control sample 3 and the control sample 4. The cross-cutting grade of the paint film after the high adhesion powder coating obtained by the preparation method of the high adhesion powder coating of the present invention is H grade, which is the same as the control sample 1, the control sample 2, the control sample 3 and the control sample 4. Therefore, the paint film after the high adhesion powder coating of the present invention is sprayed has the same excellent mechanical properties as the existing powder coating (control sample 1, the control sample 2, the control sample 3 and the control sample 4). The 60° gloss of the paint film of the high-adhesion powder coating obtained by the preparation method of the high-adhesion powder coating of the present invention after spraying is 30-35°, the 60° gloss of the paint film of the control sample 1 after spraying is 33°, the 60° gloss of the paint film of the control sample 2 after spraying is 34°, the 60° gloss of the paint film of the control sample 3 after spraying is 35°, and the 60° gloss of the paint film of the control sample 4 after spraying is 90°. Therefore, the 60° gloss of the paint film of the high-adhesion powder coating of the present invention after spraying is basically the same as that of the control sample 1, the control sample 2 and the control sample 3, but, compared with the control sample 4, the high-adhesion powder coating of the present invention has a lower gloss.
[0078] Experiment 3
[0079] Take a piece of plexiglass, divide it into 7 equal parts, and apply silicone glass glue on one side of each part; then, bond it to the 7 galvanized plates sprayed with powder coating obtained in Experiment 2, press for 10 seconds, and let it rest for 24 hours to test the bonding performance. The test items include surface tension and peeling performance, and the experimental results are listed in Table 3.
[0080] Among them, the test method of surface tension is to use a dyne pen 34 to evenly draw a 5-10cm straight line on the surface of the coating film, and observe the spreading of the ink after 2-3s. If the ink shrinks, it means that the surface tension of the coating film is less than the dyne value of the ink (34dyn / cm); if the ink spreads without shrinkage, it means that the surface tension of the coating film is greater than the dyne value of the ink (34dyn / cm); the peeling performance is tested according to the method specified in the pull-off adhesion test of GB / T 5210-2006 paints and varnishes, and a tensile machine is used to apply a tensile strength of 5MPa to horizontally stretch the glass and metal substrates to observe whether the silicone glue and the paint film are peeled off and broken.
[0081] Table 3 Peeling performance test results of different powder coatings
[0082] Sample name Surface tension (dyn / cm) Dyne pen 34 Stripping performance Performance requirements >34 Flat and no shrinkage No peeling from the paint film Embodiment 1 >34 Flat and no shrinkage No stripping Embodiment 2 >34 Flat and no shrinkage No stripping Embodiment 3 >34 Flat and no shrinkage No stripping Control Sample 1 <34 Fully retracted Partial peeling Control Sample 2 <34 Moderate contraction Partial peeling Control sample 3 <34 Fully retracted Partial peeling Control Sample 4 <34 Fully retracted Completely peeled off
[0083] It can be seen from Table 3 that the surface of the bonding layer between the paint film and the silicone glass glue after the high-adhesion powder coating obtained by the preparation method of the high-adhesion powder coating of the present invention is flat and shrinkage-free, that is, the surface tension between the paint film and the silicone glass glue after the high-adhesion powder coating obtained by the preparation method of the high-adhesion powder coating of the present invention is greater than 34 dyn / cm; however, the surfaces of the bonding layers between the paint film and the silicone glass glue after the control samples 1, 3 and 4 are sprayed are completely shrunk, and the surface of the bonding layer between the paint film and the silicone glass glue after the control sample 2 is sprayed also shows moderate shrinkage, that is, the surface tension between the paint film and the silicone glass glue after the existing powder coatings (control samples 1, 2, 3 and 4) are sprayed is less than 34 dyn / cm. After the high-adhesion powder coating prepared by the method for preparing the high-adhesion powder coating of the present invention is sprayed, the paint film is bonded to the glass panel with silicone glass glue without peeling off. After the control samples 1, 2 and 3 are sprayed, the paint film is bonded to the glass panel with silicone glass glue and partially peeled off. However, after the control sample 4 is sprayed, the paint film is bonded to the glass panel with silicone glass glue and completely peeled off. Therefore, the paint film obtained by the high-adhesion powder coating of the present invention has a large surface tension, the paint film has a strong adhesion to the silicone glass glue on the glass panel, and the paint film is firmly bonded to the glass panel.
[0084] Therefore, compared with the prior art, the beneficial effects of the present invention are as follows: the carboxyl groups in the matting aid containing stearate, the hydroxyl groups in cellulose acetate butyrate and the hydroxyl groups in the polar leveling agent of the present invention are all polar groups, and these polar groups complement the hydroxyl groups in the epoxy resin and the ester groups in the polyester resin, effectively making up for the defect of low content of polar groups on the surface of the paint film of the traditional powder coating; moreover, the carboxyl groups in the matting aid containing stearate, the hydroxyl groups in cellulose acetate butyrate and the hydroxyl groups in the polar leveling agent closely cooperate with the hydroxyl groups in the epoxy resin and the ester groups in the polyester resin, adsorb on each other, and migrate to the surface of the paint film when the powder coating is cured. On the surface, it plays a bridging role, improving the adhesion of the paint film surface; in addition, the matting aid containing stearate, cellulose acetate butyrate and polar leveling agent also promote each other with diphenyl ethyl ketone and wetting promoter, and the coordinated effect increases the surface tension of the paint film. When used on the shell of household appliances, it increases the contact area between the paint film and the glass glue on the glass panel, greatly enhances the adhesion between the paint film and the glass glue on the glass panel, and makes the glass panel firmly fixed on the shell of the household appliance, meets the installation requirements of the glass panel on the shell of the household appliance, realizes the normal production of the household appliance, and ensures the performance quality and appearance of the household appliance. The preparation method of the high-adhesion powder coating of the present invention is simple to operate, has low equipment requirements, mild process conditions, and is easy to realize industrial production.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-adhesion powder coating, characterized in that: The composition comprises the following weight percentages: Epoxy resin 25-35%, polyester resin 30-40%, matting agent 1-2%, cellulose acetate butyrate 0.3-1.0%, polar leveling agent 0.5-1%, benzoyl ketone 0.3-0.5%, wetting promoter 0.4-0.7%, filler 5-25%, titanium dioxide 5-25%, pigment 0-1%; The matting aid is a matting aid containing stearate, and the weight percentage of the stearate in the matting aid is 2-10%.
2. The high-adhesion powder coating according to claim 1, characterized in that: The high-adhesion powder coating has an average particle size of 35-45 μm.
3. The high-adhesion powder coating according to claim 1, characterized in that: The wetting promoter is methyl methacrylate-butyl acrylate copolymer.
4. The high-adhesion powder coating according to any one of claims 1 to 3, characterized in that: The epoxy resin is a bisphenol A type epoxy resin with an epoxy value of 0.110-0.130 eq / 100g.
5. The high-adhesion powder coating according to any one of claims 1 to 3, characterized in that: The polyester resin is a carboxyl-terminated saturated polyester resin having an acid value of 45-70 mgKOH / g.
6. The high-adhesion powder coating according to claim 1, characterized in that: The filler is any one or more of barium sulfate, calcium carbonate and silicon dioxide.
7. The high-adhesion powder coating according to claim 1, characterized in that: The titanium dioxide is rutile titanium dioxide.
8. The high-adhesion powder coating according to claim 1, characterized in that: The pigment is a carbon black pigment.
9. A method for preparing a high-adhesion powder coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Weigh epoxy resin, polyester resin, matting agent, cellulose acetate butyrate, polar leveling agent, benzoyl ketone, wetting promoter, filler, titanium dioxide and pigment, mix and stir evenly to obtain a mixture; 2) placing the mixture obtained in step 1) in a twin-screw extruder for melting, mixing and extrusion, wherein the temperature of the first zone of the twin-screw extruder is 100-110° C. and the temperature of the second zone is 110-120° C.; 3) Cooling, crushing, grinding and sieving the sheet extruded in step 2) to obtain a high-adhesion powder coating.
10. A use of a high-adhesion powder coating according to any one of claims 1 to 8, characterized in that: The high-adhesion powder coating is used on housings of household appliances.
Citation Information
Patent Citations
Special powder coating for household appliances and preparation method of special powder coating
CN112852252A
Toughened, modified, low-temperature-cued and low-glossiness powder coating, preparation method and application
CN106752765A